Comparison of the ICC location in the gallbladder wall in patients with cholelithiasis and patients with non-calculous changes - Spętana, Joanna; Lipiński, Artur; Jeleń, Michał (Polish Journal of Pathology, 2019)
Interstitial cells of Cajal (ICC) were first described by Santiago Ramon y Cajal over 100 years ago. They are thought to play an important role in the regulation of gastrointestinal motility. There is increasing evidence that the decline in their number in the gallbladder wall contributes to the formation of concrements. The aim of the study was to determine the exact location of interstitial cells of Cajal in the gallbladder wall in patients with calculous and non-calculous cholecystitis. Sixty-eight patients were examined, of whom 50 were cases of cholelithiasis and 18 were of non-calculous cholecystitis. The technique of immunohistochemistry with the CD117 antibody was used to determine the cells of Cajal, while to distinguish them from mast cells the technique with mast cell tryptase (MCT) was applied. Redistribution of the interstitial cells of Cajal from the muscle membrane to lamina propria of mucous tissue was observed in the cases of cholelithiasis, while in the group of non-calculous cholecystitis most of the ICC was located within the muscle tissue.